Contextual Physics Learning through Ethnoscience: Enhancing Students' Analytical Thinking in Local Culture-Based Education - Nurussaniah Nurussaniah (JURNAL PENDIDIKAN SAINS DAN APLIKASINYA, 2024)
This study investigates the integration of ethnoscience into contextual physics learning as a strategy for enhancing students’ analytical thinking skills within a local culture-based educational framework. The rapid shift toward standardized curricula in science education has progressively marginalized indigenous knowledge systems, creating a disconnect between students’ sociocultural backgrounds and formal scientific learning. Drawing on a quasi-experimental design involving 68 senior secondary school students in West Kalimantan, Indonesia, this research examines whether ethnoscience-integrated physics instruction produces measurable gains in analytical thinking compared to conventional teaching methods. Pre-test and post-test analytical thinking assessments were administered, and qualitative data were collected through classroom observations and reflective journals. Results indicate that students in the ethnoscience-integrated group demonstrated significantly higher analytical thinking scores (p < 0.05) and reported greater motivation and contextual relevance in learning. The findings affirm that embedding local cultural knowledge including traditional architecture, weaving patterns, and agricultural practices into physics instruction creates authentic learning contexts that promote deeper conceptual understanding. This study contributes to the growing body of literature on culturally responsive science education and provides practical implications for curriculum developers and educators in multicultural and indigenous communities.